1987
DOI: 10.1021/ma00174a030
|View full text |Cite
|
Sign up to set email alerts
|

Blends of polycarbonate and poly(methyl methacrylate) and the determination of the polymer-polymer interaction parameter of the two polymers

Abstract: Blends of bisphenol A polycarbonate (PC) and poly(methyl methacrylate) (PMMA) prepared by screw extrusion and solution casting have been investigated by differential scanning calorimetry and scanning electron microscopy. From the measured glass transition temperatures (Tg) and specific heat increments (ACp) at the Tg, the PMMA appears to dissolve more in the PC-rich phase than does the PC in the PMMA-rich phase. The blend appears to be near equilibrium under extrusion as well as solution-casting conditions so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
87
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 19 publications
2
87
2
Order By: Relevance
“…The blend is declared miscible if it possesses a single glass transition temperature between that of the components, while two T g s are detected in immiscible blends corresponding to phases rich in the two components. The two transition temperatures shift towards each other in an extent depending on interactions and the mutual miscibility of the phases can be calculated from this shift with the method proposed by Kim and Burns [69]. T g s determined in two of the blend series are plotted against composition in Figure 7.…”
Section: Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blend is declared miscible if it possesses a single glass transition temperature between that of the components, while two T g s are detected in immiscible blends corresponding to phases rich in the two components. The two transition temperatures shift towards each other in an extent depending on interactions and the mutual miscibility of the phases can be calculated from this shift with the method proposed by Kim and Burns [69]. T g s determined in two of the blend series are plotted against composition in Figure 7.…”
Section: Interactionsmentioning
confidence: 99%
“…The asymmetric composition dependence of structure might be related to this decrease (see Figure 6), to the change in interaction and miscibility with composition. Nevertheless, based on these data interaction cannot be estimated quantitatively, interaction parameter or mutual miscibility is difficult or impossible to calculate by the Kim and Burns [69] approach. Miscibility can also be estimated from component properties using the simple approach of group contributions, which yield the solubility parameter of the components, as described by Small [70], Hoy [71] and Hoftyzer and Van Krevelen [72].…”
Section: Interactionsmentioning
confidence: 99%
“…Previous papers [1][2][3] reported that polymethylmethacrylate (PMMA) is a potential compatibilizer for the immiscible polycarbonate/polyvinylidenefluoride (PC/PVDF) polyblends, since PMMA is known for miscibility with PVDF [4][5][6] and compatibility with PC [7][8][9]. As a rule, the interfacial adhesion and the interfacial tension of immiscible PC/PVDF blends are improved by the addition of PMMA [1][2], which concentrates in the PVDF rich phase, but also at the PVDF/PC interface.…”
Section: Introductionmentioning
confidence: 99%
“…Melt-mixed PC/PMMA pendant groups which undergo transesterification blends have been reported to be partially misciwith the carbonate bonds of PC and cause crossble 2,7 or completely immiscible, 2,4 depending on linking. However, no reaction was found on heatthe composition of the blends.…”
Section: Introductionmentioning
confidence: 99%
“…and 220ЊC. 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Furthermore, although PMMA has a pendant Different types of chemical reaction between the ester group that in principle might be able to react two polymers have been hypothesized to explain the with PC in the molten state at 250ЊC producing a formation of homogeneous PC/PMMA blends at graft copolymer (Scheme 1), evidence exists that temperatures higher than 220ЊC. 10,11,15,16 reactions of this type do not occur at this temperaMcNeill et al 5 investigated the thermal decomture in absence of a catalyst.…”
mentioning
confidence: 99%